Kultur & Kreativität: Buch als Kulturgut. Arbeitsbericht - Ann-Sophie Vorndran (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Buchwissenschaft, Professur für Buchwissenschaft, insb. E-Publishing und Digitale Märkte, 2021)
– Technology is destroying book culture - at least if one trusts the book industry's branch journals. In this, technology and culture are often discussed as separate matters, which do not seem to get together as the term culture is highly charged with value attribution. However, research on the book as cultural good is little and so the question arises: What is it that makes a book a cultural good? Its material? Its content? Or, maybe something entirely different? What role does culture itself play in this definition and why is the creative genius so important to the definition of culture? This report seeks to display the research on the book as cultural good and finds little information, which can help define it. Therefore, the term culture needs to be looked at in context of creativity and the surrounding system of the CCS.
urn:nbn:de:bvb:29-opus4-170303
Keywords: 020; Buch; Kulturgüter